2021
DOI: 10.3390/applnano2010002
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Shelf Life of Strawberries by the Sonochemical Coating of their Surface with Nanoparticles of an Edible Anti-Bacterial Compound

Abstract: The current paper presents the coating of harvested strawberries with edible nanoparticles of Chitosan. The NPs were formed by the application of ultrasonic waves on an acidic solution of chitosan. In a one-step process the nanoparticles were created and subsequent to their formation they were deposited on the strawberries surface. The shelf life of the NPs coated was compared with the deposition of the same amount of non-sonicated chitosan, i.e., coating of individual chitosan molecules on the fruit. The char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Coating the fruit with substances such as chitosan increases cytochrome oxidase activity by reducing the internal oxygen of the fruit, and this enzyme can greatly reduce the rate of decomposition of ascorbic acid [60]. Similar results of reduction in ascorbic acid concentration during storage of strawberry fruit were observed by Khodaei et al [61] and Belal Abu Salha and Gedanken [62].…”
Section: Ascorbic Acid Contentmentioning
confidence: 59%
“…Coating the fruit with substances such as chitosan increases cytochrome oxidase activity by reducing the internal oxygen of the fruit, and this enzyme can greatly reduce the rate of decomposition of ascorbic acid [60]. Similar results of reduction in ascorbic acid concentration during storage of strawberry fruit were observed by Khodaei et al [61] and Belal Abu Salha and Gedanken [62].…”
Section: Ascorbic Acid Contentmentioning
confidence: 59%
“…Strawberry (Fragaria × ananassa) is an economically important crop worldwide [1,2]. It has a great nutritional value because it contains minerals, vitamins, flavonoids, and phenolic compounds with beneficial biological properties, for instance antioxidant, anticancer, and anti-inflammatory activities [3,4]. Strawberry has tremendous prospects for commercial use, e.g., for the extraction of natural color with great potential for diverse value-added processed products [5].…”
Section: Introductionmentioning
confidence: 99%
“…But the elongation percentage of these films increased up to 58.33% with oil addition. Abu Salha & Gedanken, 2021 have reported that the mechanical properties of banana puree‐based films improve their tensile strength, elongation percentage from 2.7 to 4.3 MPa and 13 to 16% with an increase in pectin concentration from 0.5 to 0.75% to its film formulation. Plasticizer used in films can influences the mechanical properties of film as it has a different molecular weight, size, and hydrophilicity (Go & Song, 2020).…”
Section: Resultsmentioning
confidence: 99%